2015
DOI: 10.1371/journal.pone.0121519
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of TcCYS4 Modified by Variations in pH and Temperature Can Affect Symptoms of Witches’ Broom Disease of Cocoa, Caused by the Fungus Moniliophthora perniciosa

Abstract: The phytocystatins regulate various physiological processes in plants, including responses to biotic and abiotic stresses, mainly because they act as inhibitors of cysteine proteases. In this study, we have analyzed four cystatins from Theobroma cacao L. previously identified in ESTs libraries of the interaction with the fungus Moniliophthora perniciosa and named TcCYS1, TcCYS2, TcCYS3 and TcCYS4. The recombinant cystatins were purified and subjected to the heat treatment, at different temperatures, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous observations have shown that serpins from barley and wheat grains, for example, are apparently inactivated at more acidic pH levels ( Roberts et al., 2003 ). Changes in acidity and temperature are efficient strategies for inactivating plant defense proteins during Theobroma cacao-Moniliophthora perniciosa interaction ( Freitas et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations have shown that serpins from barley and wheat grains, for example, are apparently inactivated at more acidic pH levels ( Roberts et al., 2003 ). Changes in acidity and temperature are efficient strategies for inactivating plant defense proteins during Theobroma cacao-Moniliophthora perniciosa interaction ( Freitas et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that variations in pH and temperature can affect the oligomerization of TcCYS4 modifying the inhibitory activity this cystatin against PLPCs engaged in PCD, and affect symptoms of witches’ broom disease of cocoa, caused by the fungus M . perniciosa [ 54 ]. Cystatin levels also decrease in mature tissues, while the main difference concerns the protein levels between infected and uninfected tissues during the transition from green broom to dry broom, which corresponds to the transition from biotrophic to necrotrophic mycelium of M .…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine-protease inhibitors are candidates to treat SARS-CoV and MERS-CoV [ 12 ]. Protease inhibitors from Theobroma cacao have been characterized and described as papain like protease inhibitors, called TcCYS3 and TcCYS4, two thermally stable cystatins [ 13 ] that can also inhibit the growth of Moniliophtera perniciosa [ 14 ].…”
Section: Introductionmentioning
confidence: 99%